Sustainable production systems strategies in the Mixteca Alta region of Oaxaca - Ortiz-Jiménez, Bersaín; Martínez-Santiago, Daniel (Revista Mexicana de Ciencias Agrícolas, 2026)
In Mexico, the problems faced by rural communities lie in their high institutional economic dependence. The integration and participation of producers and society represent an opportunity to use natural resources sustainably. The objective was to describe proposals for sustainable production practices as possibilities for producers in the rural communities of Chalcatongo de Hidalgo to apply in the management of productive projects and in the improvement of the local economy. Forests have the capacity to capture carbon dioxide (CO2), which is traded in exchange for economic resources. Nevertheless, it is required to have a solid organization, strong commitment, constant effort and effective collaboration of social capital. After a review of relevant documents, database analysis, and participant observation, it was determined that it is feasible to apply sustainable productive practices to the management of sustainable projects and local economies; however, commitment, awareness, responsibility and the implementation and strengthening of social capital are essential.
Keywords: carbon capture; rural communities; natural resources; sustainable